The legal notion of “second-order violence”: a legislative novelty in the protection of rights and freedoms. Regarding de relevance of expanding the principle of indemnity against reprisals linked to sexist violence - Madrid Pérez, Antonio (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
The introduction of the notions of “second-order violence” and “second-order discrimination” in two laws at the end of 2020 by the Parliament of Catalonia means a legislative novelty at the state and international level. Through these new legal concepts, it is proposed to expand the protection against reprisals that are sometimes exercised on those who confront situations of sexist violence and / or those who give support to the victims, even if they do not do so within the framework of an administrative procedure or a judicial procedure. The inclusion of these concepts in two laws focused on the eradication of sexist violence and on equal treatment and non-discrimination opens a debate about whether the expansion of the scope of protection is a measure that contributes to improving the effectiveness of the mechanisms to protect rights and freedoms.